Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.pone.0257480
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coronavirus disease 2019 on myopic progression in children treated with low-concentration atropine

Abstract: Purpose The outbreak of coronavirus disease 2019 (COVID-19) has caused many children to stay indoors. Increased near work and insufficient outdoor activities are considered important risk factors for myopic progression. This study aimed to compare the changes in myopic progression before and after COVID-19 in children treated with low-concentration atropine. Methods The records of 103 eyes of 103 children who were treated with low-concentration atropine eye drops were retrospectively reviewed. We classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(75 citation statements)
references
References 23 publications
(26 reference statements)
3
60
1
Order By: Relevance
“…A total of seven studies were conducted in cohorts of the same group of children at different ages (Longitudinal cohort), the other four studies were conducted in cohorts of the different groups of children at the same age (Crosssectional cohorts). All studies without myopia preventive intervention found at least one of the following outcomes: increased myopia prevalence (ranging from 7.5-20.5% with a trend of more rising of prevalence in younger age groups (29)), increased myopia incidence (from 7.5% to 15.3%), greater myopia progression (negative SER change ranging from 0.05-0.98 D (29,(31)(32)(33)(34)(35)(36)38) or negative rate of SER changes ranging from 0.05-0.1 D/month (30,37)) during the COVID-19 lockdown. With preventive interventions, a study in Taiwan reported stable myopia prevalence throughout the COVID-19 lockdown (39).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of seven studies were conducted in cohorts of the same group of children at different ages (Longitudinal cohort), the other four studies were conducted in cohorts of the different groups of children at the same age (Crosssectional cohorts). All studies without myopia preventive intervention found at least one of the following outcomes: increased myopia prevalence (ranging from 7.5-20.5% with a trend of more rising of prevalence in younger age groups (29)), increased myopia incidence (from 7.5% to 15.3%), greater myopia progression (negative SER change ranging from 0.05-0.98 D (29,(31)(32)(33)(34)(35)(36)38) or negative rate of SER changes ranging from 0.05-0.1 D/month (30,37)) during the COVID-19 lockdown. With preventive interventions, a study in Taiwan reported stable myopia prevalence throughout the COVID-19 lockdown (39).…”
Section: Resultsmentioning
confidence: 99%
“…A total of five studies monitored the changes in axial length (AL) during the COVID-19 lockdown. (31,32,34,36,37) Two of these studies reported an increase in AL during the lockdown (ranging from 0.08-0.31 mm) (31,32). Another two studies found faster AL elongation during the lockdown (0.47 mm/year compared to 0.29 mm/year (36), the rate of AL increase ranging from 0.03-0.05 mm/month (37)).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations